The Impact of Understanding, Religiousity, and Faith towards the Intention to Pay Professional Zakat by Muzakki at Lembaga Amil Zakat Inisiatif Zakat Indonesia (LAZ-IZI) Balikpapan City, East Kalimantan - Ana Mulyana; Sri Wahyuni (Universitas Muhammadiyah Mataram, 2018)
The dynamics of Muslim society affects the development of the discourse regarding Islamic sharia, including that of professional zakat, which is now enforced in the province of East Kalimantan, where many Muslim work as professionals. This research explored the impact of understanding, religiousity, and faith towards the intention to pay professional zakat by muzakki. The research was quantitative using the formula of multiple linear regression analysis. The data were collected through questionnaires from the sample of 94 muzakki, taken using Slovin formula, out of the population of 1,516 professional muzakki at Lembaga Amil Zakat Inisiatif Zakat Indonesia (LAZ-IZI) Balikpapan City, East Kalimantan. The findings revealed that understanding had a positive impact but not significant on the intention to pay professional zakat as indicated with t_(calculation ) 1,577 <t_tabel1,986 with the level of significance = 0,118 higher than α = 0,05; religiosity has a positive impact and significant on the intention to pay professional zakat as indicated with t_calculation 2,724>t_tabel1,986 with significance level = 0,008 lower than α = 0,05; and faith has a positive impact and significant on the intention to pay professional zakat as shown with t_(calculation ) 2,376>t_tabel=1,986 with significance level = 0,020 lower than α = 0,05. In sum, understanding has a positive but not significant impact on the intention to pay professional zakat, and both religiosity and faith have a positive and significant impact on the intention to pay professional zakat among professional muzakki in Balikpapan, East Kalimantan.